PENCEMARAN AIR TANAH AKIBAT PEMBUANGAN LIMBAH DOMESTIK DI LINGKUNGAN KUMUH - Harmayani, Kadek Diana; Konsukartha, I G. M. (Jurnal Natah, 2007)
The spreading pattern of inhabitant in Banjar Ubung Sari, it is causes expanding of human settlements.It’ts cause the poor sewerage disposal of household waste such as toilet and kitchen are not organizedbetter. The waste can also cause contamination of ground water that influences the happening ofspreading some contagion.Research result of well water drill do not contaminated by bacterium, so its can consume to becomedrinking water. For water coming from well dig most impure by bacterium of E.Coli and bacterium ofColiforms, so that the water coming from well dig some of may not consume to become drinking water.But most (82, 98 %) resident of Banjar Ubung Sari are use water of PDAM for everyday requirement.The problems of waste-disposal of urine and faeces are planned by a tank of septik which located inwalkway, this planning is done because insufficient land around the house yard. .Tthis matter also isconducted to avoid the happening of environmental problem, health problem, and to minimize the expenseof septik tank cleaning for the people around.